Search engine optimization - Elmansy, Rafiq (2013)
Learn to build an SEO-friendly website, add meta tags to your pages, optimize your site's content, create a Google Analytics account, and apply SEO to WordPress blogs
Understanding the SEO process -- Preparing your website for SEO -- Building a SEO friendly website -- Mastering keywords -- Building on-page SEO -- Building off-page SEO -- Working with content -- Working with Google analytics -- Using search engine webmaster tools -- Working with social media and SEO -- Working with AdWords -- Applying SEO to WordPress blogs -- Monetizing your website -- Building and managing an SEO team
Includes index
1 14
Keywords: Internet marketing; Internet marketing; Internet searching; Internet searching; Search engines; Search engines; Web search engines; Web search engines; Web sites -- Registration with search engines; Web sites -- Registration with search engines